Hölderlin: Between Kant and the Greeks - Àlex Mumbrú Mora (Humanities)
In Hyperion, or the Hermit in Greece, Hölderlin introduces two narrative planes: the description of action and the reflection (or memory) of past events. The transition between these points of view is facilitated by the extensive use of metaphor. This paper examines Hölderlin’s use of metaphorical language through Plato’s conception of beauty as a link between the sensible and intelligible worlds and Kant’s notion of the “aesthetic idea” as an imaginative representation that “occasions much thinking” (viel zu denken veranlasst). This analysis shows how both sources constitute the theoretical framework for the construction of a New Mythology, as outlined in Das älteste Systemprogramm des deutschen Idealismus.